Self–management Behavior of Chronic Kidney Disease Patients without Dialysis Treatment Level 1–4 in Pho, Nongkaew and Phonkhwo Sub–District, Mueng District, Sisaket Province - Pochai, Sivilai; Kingkeaw, Jintana; Yomsriken, Nakanda (Medical Journal of Sakon Nakhon Hospital, 2024)
The aim of this research was to study the level of self–management behavior and ability to perform activities of daily living in 86 patients with stage 1–4 of chronic kidney disease without dialysis treatment and to study the relationship between their personal factors, self–management behavior and ability to perform activities of daily living in Pho, Nongkaew, and Phonkhwao sub district, Mueng district, Sisaket province. The samples were purposive selected. The research tool was the questionnaire with the reliability of 0.79 calculated by Cronbach’s alpha coefficient. The quantitative data were analyzed by using the descriptive statistics. The correlations were analyzed by using the Chi–square test and the Pearson product–moment correlation. The result showed that the overall self–management behavior of the samples were at the low level with an average of 1.93 (S.D. = 0.25). Sixty–nine patients (80.2%) had the abilities to perform activities of daily living at a level of slight dependence. The correlation between their abilities to perform activities of daily living and self–management was not found. There was no correlation between their self–management behaviors and personal factors, sex, age, marriage status, educational level, occupation, income, patient right and stage of the disease. The findings suggested that patients’ self–ability to perform activities of daily living should be encouraged in order to improve their self–managements and to apply to perform in daily living effectively.